Review of In Quest of Justice: Islamic Law and Forensic Medicine in Modern Egypt - Fancy, Nahyan (JAOS, 2025)
In Quest of Justice: Islamic Law and Forensic Medicine in Modern Egypt. By Khaled Fahmy. University of California Press, 2018. Pp. xiii + 377. $39.95, £34 (cloth); $29.95, £25 (paper)